PEREPSI MASYARAKAT TERHADAP PENGUNJUNG “ CAFE GOLI-GOLI ” DIKELURAHAN BAGAN TIMUR KECAMATAN BANGKO KABUPATEN ROKAN HILIR - ", Roriana; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
At the present time, the influence of western culture (westernization) too in the adorable among young people make increasingly decaying values and norms. Thus, the moral behavior of the young generation is not in accordance with the norms that exist in society. Sexual problems that occur in various areas also occur in the East Village community Chart District of Bangko Rokan Hilir (visitors Cafe Goli-goli). The purpose of this research is to gain "of how the public perception of the visitors' Cafe Goli-Goli". This research was conducted at RT 10 RW 03 Chart East Village District of Bangko Rokan Hilir. In this study, the research subjects were indigenous East Village Chart already many as 15 respondents and who became Community Leaders in the East Village and supplemented Chart of visitors "Cafe Goli-Goli" A total of 8 visitors, to collect data researchers using the method of observation and in-depth interviews using the interview guide. In analyzing the research data the researcher uses descriptive qualitative analysis. Results showed socioeconomic visitors economic classified medium, it can be seen from the income they earn. And the public perception of dating behavior of visitors Cafe Goli-Goli No Good. Their reasons because it will lead to promiscuity, community hopes that the parties are more assertive in supervising authorities Cafe, what if a visitor finds that violate the values and norms that exist in the society in firm sanctions so that no pornography.Keyword: Public Perception, Visitor Behavior Cafe Goli-Goli.